ZAKAT SAHAM DAN OBLIGASI - Yenni Samri Juliati (Studia Economica : Jurnal Ekonomi Islam, 2015)
Shares is a proof that states a person has part in limited company (PT). Shareholder has right of  profit that is generated by company. Bonds is long-term debt securities that gives reward periodically and will be refund of principal at maturity. The obligation of zakat on shares and bonds is based on the obligation of zakat on wealth and trade which is said in the Qur'an Surah al-Baqarah verse 267, the obligation of zakat stocks and bonds is about 2.5%.